Voices from Home: Stories of Routine, Rhythm, and Responsive Parenting in ECD - Sharma, Rati (Journal of Durgalaxmi, 2025)
This research explores how daily routines, rhythms, and responsive parenting at home influence children’s development in Early Childhood Education. Focusing on families in urban Kathmandu, Nepal, the study examines parents’ practices, beliefs, and experiences in supporting their children’s cognitive, social-emotional, and behavioral growth. Using interviews and observations, the research highlights how structured daily activities, consistent caregiving, and responsive interactions create a nurturing environment that nurtures children’s learning and well-being. The study also identifies challenges parents face, including time constraints, limited resources, and balancing work and caregiving responsibilities. Findings emphasize the importance of culturally grounded parenting practices and offer insights for educators and policymakers to support families in creating positive developmental environments for young children.